Risks and implications of bovine spongiform encephalopathy for the United States: Insights from other countries - Fox, John A.; Hanawa Peterson, Hikaru (My University, 2008)
BSE has not been found in the US* but current detection efforts provide little assurance that it does not exist at a low level. The US has taken precautionary measures to reduce the risk of importing the disease and the risk of the disease spreading if it were to be found. Those measures include a ban on feeding ruminant protein to ruminants—a measure the General Accounting Office concluded was not adequately enforced and which failed to halt the disease in the UK. We present an overview of BSE in the UK, the EU, and Japan and present an argument for additional precautionary measures in the US.
Keywords: Mad cow disease; BSE; Food safety; Bovine spongiform encephalopathy